2015
DOI: 10.1002/cbin.10466
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin‐like growth factor‐1 (IGF‐1) promotes myoblast proliferation and skeletal muscle growth of embryonic chickens via the PI3K/Akt signalling pathway

Abstract: During embryonic development, IGF-1 fulfils crucial roles in skeletal myogenesis. However, the involvement of IGF-1-induced myoblast proliferation in muscle growth is still unclear. In the present study, we have characterised the role of IGF-1 in myoblast proliferation both in vitro and in vivo and have revealed novel details of how exogenous IGF-1 influences myogenic genes in chicken embryos. The results show that IGF-1 significantly induces the proliferation of cultured myoblasts in a dose-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 27 publications
4
87
0
1
Order By: Relevance
“…In this study, we observed that both USCs-EVs and iMSCs-EVs promoted C2C12 myoblast proliferation. Previous studies reported that VEGF, HGF and IGF-1 were not only potential proangiogenic factors but also promoted myoblast proliferation [53][54][55][56][57][58][59]. In the present study, we found that VEGF, HGF and IGF-1 were loaded in the USCs-EVs.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, we observed that both USCs-EVs and iMSCs-EVs promoted C2C12 myoblast proliferation. Previous studies reported that VEGF, HGF and IGF-1 were not only potential proangiogenic factors but also promoted myoblast proliferation [53][54][55][56][57][58][59]. In the present study, we found that VEGF, HGF and IGF-1 were loaded in the USCs-EVs.…”
Section: Discussionsupporting
confidence: 67%
“…The ability of IGF-1 to accelerate cell viability was also found in the previous literature. A report declared that IGF-1 promoted myoblast proliferation [27]. Furthermore, Yan et al demonstrated that IGF-1 promoted cell proliferation of human periodontal ligament stem cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…; Yu et al . ). We were able to measure tarsus and wing length of nestlings, respectively, from days 7 and 8 post‐hatch onwards.…”
Section: Discussionmentioning
confidence: 97%